Two new variables measured at rest to predict running performance - Legaz Arrese, A. (New Studies in Athletics, 2007)
Sport scientists and coaches both seek variables that measure the fitness of athletes. Numerous physiological variables have been shown to predict performance, particularly in endurance running. However, the majority of studies are on heterogeneous groups and few longitudinal studies exist The author's fact-finding group has recently published several investigations on homogeneous groups of elite runners evaluated over several seasons. Their focus was on measurement of the left ventricular internal diameter of end-diastole (LVIDd) and lower limb skinfolds. Findings related to LVIDd include that the values in sprint and endurance runners increase with training and that the highest values are observed during the season of the athlete's best performance. It was also found that the assessment of lower limb skinfolds may be useful for predicting performance. Both sets of parameters can be simply measured at rest and it is recommended that coaches include these in the battery of tests for elite runners.